2023
DOI: 10.1088/1748-9326/ad08f8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating equity and justice in low-carbon energy transitions

Sage Kime,
Veronica Jacome,
David Pellow
et al.

Abstract: A low-carbon energy transition is essential for mitigating climate change, but can also cause energy justice and equity impacts on Black, Indigenous, and People of Color (BIPOC), low-income, and other frontline communities. Examples include exacerbating energy burden, inaccessibility and unaffordability of low-carbon energy and electric end-use technologies, property value loss and displacement from renewable energy siting, and unequal health benefits and employment losses from fossil fuel retirement. To avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…As also highlighted, legacy energy production infrastructure militates against the incentive to adopt RE options as the government seems to lag in investing in new tech-driven facilities required for RE production. 51 For instance, this is true in wind energy, which is hampered by farm location. Akinbami, Oke and Bodunrin 20 indicated that most wind farms in South Africa are often in remote areas, making a connection to the grid challenging.…”
Section: Challenges For Effective Transition To Renewable Energy In S...mentioning
confidence: 99%
“…As also highlighted, legacy energy production infrastructure militates against the incentive to adopt RE options as the government seems to lag in investing in new tech-driven facilities required for RE production. 51 For instance, this is true in wind energy, which is hampered by farm location. Akinbami, Oke and Bodunrin 20 indicated that most wind farms in South Africa are often in remote areas, making a connection to the grid challenging.…”
Section: Challenges For Effective Transition To Renewable Energy In S...mentioning
confidence: 99%
“…Another issue is the subjectivity of selecting metrics. Kime et al (2023) in their study, aiming to review metrics addressing equity in energy transition highlighted that this may cause ignoring important metrics while studying one of the dimensions. Whether it was unintentional or not, this may affect decision-making and reduce transparency.…”
Section: Challenges Associated With Metrics Identificationmentioning
confidence: 99%
“…This is also another reason why these metrics are more common than other metrics. Also, with the increase in interest in justice, and equitable issues as well (Barlow, J, Tapio, R, Tarekegne, B, 2022), more metrics have been used in studies to assess the social impact, some of these metrics require qualitative tools to be measured, this has increased the share of social metrics used (Kime, S et al, 2023).…”
Section: Challenges Associated With Metrics Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy justice is frequently described as consisting of three major tenets: distributional justice, focused on how benefits and burdens are distributed across populations; recognition justice, which recognizes vulnerable communities and the causes of past and present inequities; and procedural justice, which focuses on just processes and inclusion in decision making processes [9]. Energy justice scholars have described important dimensions of equity including health, access, and livelihood, and have suggested that key components of an equitable energy transition include renewable energy deployment, fossil fuel infrastructure retirement, transportation electrification, and residential building decarbonization [10]. Others have suggested additional dimensions including consumer energy consumption, wealth creation, ownership, and autonomy; multi-scalar supply chain equity; and comparative country-level equity [11].…”
Section: Introductionmentioning
confidence: 99%